Cardiac involvement, morbidity and mortality in hereditary transthyretin amyloidosis because of p.Glu89Gln mutation. Issue 9 (September 2020) - Gospodinova, Mariana; Sarafov, Stayko; Chamova, Teodora; Kirov, Andrey; Todorov, Tihomir; Nakov, Radislav; Todorova, Albena; Denchev, Stefan; Tournev, Ivailo
Abstract : Background: Hereditary transthyretin amyloidosis is a systemic infiltrative disease, caused by a mutation in the transthyretin gene. p.Glu89Gln is the most common mutation in the Balkan countries. Methods: We evaluated the clinical manifestations, cardiac involvement, morbidity and mortality in 78 patients with p.Glu89Gln mutation, verified through a DNA analysis. Clinical assessment, electrocardiogram and echocardiography were performed at the time of diagnosis. The patients have been followed for 30 months. Results: All included patients were Caucasian, 39 (50%) – men, with median age at diagnosis of 56 years (42–73), median age at onset -- 53 years (35–69), starting significantly earlier in men (4.36, P  = 0.004). Cardiac and neurological involvement was found in 74 (95%) patients. Pathological ECG was present in 65 (84%) patients, infarct pattern in 43 (56%), low voltage in 24 (31%). Echocardiography revealed an infiltrative cardiomyopathy with restrictive filling in 31 (40%) and ejection fraction less than 50% in 20 (27%) patients. Twenty-two patients (28%) died: 14 (64%) because of advanced heart failure, 6 (27%) died suddenly, 2 (9%) from an ischemic stroke. The median age at death was 58.5 years (52–72). No statistically significant sex difference in survival was observed; a significant difference in survival was found for the New York Heart Association class, familial amyloidotic polyneuropathy stage, ejection fraction, filling pattern and tafamidis treatment. Conclusion: Cardiac involvement is common and has significant prognostic implications in the evaluated patients with p.Glu89Gln mutation. Heart failure and rhythm disturbances are the main causes of death. An earlier identification of the disease is crucial to improve prognosis.